2008
DOI: 10.2460/javma.232.4.553
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hemangiosarcoma in anemic dogs with a splenic mass and hemoperitoneum requiring a transfusion: 71 cases (2003–2005)

Abstract: In this clinical population of dogs, prevalence of hemangiosarcoma was higher than in other studies. Dogs with hemangiosarcoma in this study had significantly lower TS concentrations and platelet counts at the time of admission, compared with values for dogs with other splenic masses. No other markers were useful in differentiating dogs with hemangiosarcoma. It is important to discuss the prevalence of and poor prognosis associated with hemangiosarcoma with owners when they are contemplating whether to proceed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
102
2
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(132 citation statements)
references
References 13 publications
17
102
2
7
Order By: Relevance
“…About 50 per cent of splenic submissions to pathology laboratories demonstrate benign changes (eg, haematoma [Fig 6] and nodular hyperplasia) and the remaining 50 per cent are malignancies. About 25 per cent of dogs presenting with non-traumatic haemoabdomen have a benign haematoma rather than a malignancy (Hammond and Pesillo-Crosby 2008, Aronsohn and others 2009). Haemangiosarcomas account for up to 80 per cent of malignancies, with the remainder comprising lymphomas, mast cell tumours, leiomyosarcomas, fibrosarcomas, osteosarcomas and malignant fibrous histiocytomas (Spangler and Kass 1997).…”
Section: Specific Splenic Conditionsmentioning
confidence: 99%
“…About 50 per cent of splenic submissions to pathology laboratories demonstrate benign changes (eg, haematoma [Fig 6] and nodular hyperplasia) and the remaining 50 per cent are malignancies. About 25 per cent of dogs presenting with non-traumatic haemoabdomen have a benign haematoma rather than a malignancy (Hammond and Pesillo-Crosby 2008, Aronsohn and others 2009). Haemangiosarcomas account for up to 80 per cent of malignancies, with the remainder comprising lymphomas, mast cell tumours, leiomyosarcomas, fibrosarcomas, osteosarcomas and malignant fibrous histiocytomas (Spangler and Kass 1997).…”
Section: Specific Splenic Conditionsmentioning
confidence: 99%
“…Several studies have reported approximately 70% of dogs with non-traumatic hemoperitoneum had hemangiosarcoma [13]. Hemoperitoneum is reported in 63–80% of dogs with hemangiosarcoma, compared with only 30% of dogs with benign splenic masses [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25][26] There have been no studies specifically evaluating the treatment of dogs with grossly metastatic HSA, a common presentation in the cases of HSA. 8,10,12 Nonresectable, primary, noncutaneous HSA appears to carry a negative prognosis for overall survival (OS), yet the use of chemotherapy or palliative radiation therapy has been largely unexplored. 27 This study evaluated the efficacy of a combination chemotherapy protocol comprised of doxorubicin, dacarbazine, and vincristine (DAV) for the treatment of advanced-stage canine noncutaneous HSA.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Many patients present with internal bleeding due to tumor rupture or disseminated intravascular coagulation. 2,[9][10][11][12] Surgery may be palliative to arrest active hemorrhage, but does not provide long-term survival for the majority of cases with visceral involvement. 8,11,13,14 Chemotherapy in the adjuvant setting has been evaluated in various clinical studies and has shown promise in prolonging life after surgical resection of the primary HSA lesion.…”
Section: Introductionmentioning
confidence: 99%